Identification of Reticulocyte Binding Domain of Plasmodium ovale curtisi Duffy Binding Protein (PocDBP) Involved in Reticulocyte Invasion - Hoque, Mohammad Rafiul; Nyunt, Myat Htut; Han, Jin-Hee; Muh, Fauzi; Lee, Seong-Kyun; Park, Ji-Hoon; Lu, Feng; Park, Won Sun; Han, Eun-Taek; Na, Sunghun (Frontiers in Cellular and Infection Microbiology, 2021)
The Plasmodium ovale curtisi (Poc) prevalence has increased substantially in sub-Saharan African countries as well as regions of Southeast Asia. Poc parasite biology has not been explored much to date; in particular, the invasion mechanism of this malaria parasite remains unclear. In this study, the binding domain of the Duffy binding protein of P. ovale curtisi (PocDBP) was characterized as an important ligand for reticulocyte invasion. The homologous region of the P. vivax Duffy binding protein in PocDBP, named PocDBP-RII herein, was selected, and the recombinant PocDBP-RII protein was expressed in an Escherichia coli system. This was used to analyze reticulocyte binding activity using fluorescence-activated cell sorting and immune serum production in rabbits. The binding specificity was proven by treating reticulocytes with trypsin, chymotrypsin and neuraminidase. The amino acid sequence homology in the N-terminal Cys-rich region was found to be 44% between PvDBP and PocDBP. The reticulocyte binding activity of PocDBP-RII was significantly higher than the erythrocyte binding activity and was concentration dependent. Erythrocyte binding was reduced significantly by chymotrypsin treatment and inhibited by an anti-PocDBP-RII antibody. This finding suggests that PocDBP may be an important ligand in the reticulocyte invasion process of P. ovale curtisi.